Geochemical Correlation of Mishrif Formation in AL-Nasiriyah Oil Field/ South of Iraq - Al-Ameri, TH.K; Al- Zaidi, M.D (Iraqi Journal of Science, 2023)
Gas Chromatography GC, Gas Chromatography–Mass spectrometry GC/MS techniques used for analysis of the crude oils that taken from (10) producing wells in Nasiriyah oil field including (NS-1, NS-3, NS-4, NS-5, NS-6, NS-7, NS-8, NS-9, NS-10, and NS-12) from Mishrif reservoir . This reservoir is one of the important reservoirs in Al-Nasiriyah oil field, and it will be the main subject in the current study in order to provide information of crude oil analysis in this area, also to provide information on its characterizations. Mishrif Formation is one of the principle carbonate reservoir in central and southern Iraq. It is part of the wasia group and widespread throughout the Arabian gulf, It is deposited during Cenomanian-Early Turonian cycle with equivalence to Upper Sarvak reservoirs in Iran and the Natih Formation in Oman,This formation in central and southern Iraq is represented in many oil fields such as, Buzergan, Amara, Halfaya, Majnoon, Rumaila, West Qurna, and Nasiriyah. The analysis of various bulk parameters such as (API gravity ,Sulfur content ,Crude oil compositions and Stable carbon isotope compositions (δ 13C ‰))and biomarker parameters such as (Alkanes and Acyclic Isoprenoid Ratios, Terpanes ,and Steranes) shows that the all oil samples are represented one group, non-biodegraded, marine, and non-waxy deposits derived from carbonate source rocks deposited in anoxic marine environment, these oils are from Jurassic, with similar level of thermal maturity ,Hence the most appropriate sources for this crude oil may be Sargelu Formation.